Primary Care–Mental Health Integration Programs in the Veterans Affairs Health System Serve a Different Patient Population Than Specialty Mental Health Clinics - Johnson-Lawrence, Vicki D. (Physicians Postgraduate Press, Inc., 2012)
Objective: To assess whether Primary Care–Mental Health Integration (PC-MHI) programs within the Veterans Affairs (VA) health system provide services to patient subgroups that may be underrepresented in specialty mental health care, including older patients and women, and to explore whether PC-MHI served individuals with less severe mental health disorders compared to specialty mental health clinics. Method: Data were obtained from the VA National Patient Care Database for a random sample of VA patients, and primary care patients with an ICD-9-CM mental health diagnosis (N = 243,806) in 2009 were identified. Demographic and clinical characteristics between patients who received mental health treatment exclusively in a specialty mental health clinic (n = 128,248) or exclusively in a PC-MHI setting (n = 8,485) were then compared. Characteristics of patients who used both types of services were also explored. Results: Compared to patients treated in specialty mental health clinics, PC-MHI service users were more likely to be aged 65 years or older (26.4% vs 17.9%, P < .001) and female (8.6% vs 7.7%, P = .003). PC-MHI patients were more likely than specialty mental health clinic patients to be diagnosed with a depressive disorder other than major depression, an unspecified anxiety disorder, or an adjustment disorder (P < .001) and less likely to be diagnosed with more severe disorders, including bipolar disorder, posttraumatic stress disorder, psychotic disorders, and alcohol or substance dependence (P < .001). Conclusions: Primary Care–Mental Health Integration within the VA health system reaches demographic subgroups that are traditionally less likely to use specialty mental health care. By treating patients with less severe mental health disorders, PC-MHI appears to expand upon, rather than duplicate, specialty care services.